The role of the Mediterranean diet on weight loss and obesity-related diseases - Estruch, Ramon; Ros, Emilio (Reviews in endocrine & metabolic disorders, 2020)
Pandemic obesity is a major public health problem because of its association with non-communicable diseases and all-cause mortality, which can be improved/delayed with weight loss. Thus, several scientific societies and governments have launched guidelines to reduce body weight and adiposity or, at least, to avoid weight gain. In spite of the abundant literature on the topic, there is still controversy on the relative roles of fat and carbohydrate in the diet on weight gain. Present recommendations to avoid weight gain and obesity are directed to reduce intake of total energy variably and of total fat to <30% of energy, in spite on the lack of evidence of protection against cardiovascular disease (CVD) and mortality. By contrast, both high and low carbohydrate diets are associated with CVD and all-cause mortality in prospective studies, with a safe intake level at ≈50% of energy. Many popular diets with widely different macronutrient composition, including the Mediterranean diet, have been used in obesity; when energy-restricted, all result in similar modest weight loss at 6 months, but the effects are largely lost at 12 months. The Mediterranean diet is a plant-based, high-fat, high-unsaturated fat dietary pattern that has been consistently associated with lower rates on non-communicable diseases and total mortality in prospective studies and with reduced CVD in the PREDIMED trial. For this merits above other diets, this dietary pattern might also be used advantageously for weight loss. The results of the PREDIMED and PREDIMED-Plus randomized controlled trials on adiposity variables in high-risk populations are discussed.